2010
DOI: 10.1248/bpb.33.1028
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide Attenuates Airway Hyperresponsiveness and Eosinophilic Inflammation in a Murine Model of Allergic Asthma

Abstract: Bronchial asthma has clinical manifestations, which include variable degrees of airflow obstruction, airway hyperresponsiveness, and airway inflammation.1) The inflammatory process in asthma is dominated by T helper-2 (Th2) cells which produce interleukin-4 (IL-4), IL-5, and IL-13. 2)Thalidomide was synthesized in 1954 by CIBA Pharmaceutical Company, and prescribed as a sedative, tranquiliser, and antiemetic for morning sickness. Because the highest risk for teratogenicity arose when the drug was taken between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Airway hyperresponsiveness was significantly decreased in pomalidomide (0.8 mg/mL) treatment as compared with pomalidomide (0.4 mg/mL).In addition, according to the previous studies, there is a positive relationship between the thickness of the ASM layer with airway responsiveness also between the regulator of inflammatory cells and the level of airway hyperresponsiveness. 4,38 In addition, histological H&E staining and Masson's trichrome analysis of the airways tissues displayed that there was additional deposition of collagen in the asthmatic rat administered with the pomalidomide treatment. Several lines of evidence demonstrated too much production of mucus and collagen and thus augmentation the thickness of airway wall as one of the important symptoms that occur in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Airway hyperresponsiveness was significantly decreased in pomalidomide (0.8 mg/mL) treatment as compared with pomalidomide (0.4 mg/mL).In addition, according to the previous studies, there is a positive relationship between the thickness of the ASM layer with airway responsiveness also between the regulator of inflammatory cells and the level of airway hyperresponsiveness. 4,38 In addition, histological H&E staining and Masson's trichrome analysis of the airways tissues displayed that there was additional deposition of collagen in the asthmatic rat administered with the pomalidomide treatment. Several lines of evidence demonstrated too much production of mucus and collagen and thus augmentation the thickness of airway wall as one of the important symptoms that occur in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The suppression activity of all ZM compounds against LPS-induced TNF-α production is mainly attributed to the isoindoline1,3-dione moiety in the ZM compounds. It has been shown that phthalimide (isoindoline1,3-dione) and thalidomide analogues do inhibit synthesis of TNF-α from LPS-activated macrophages through impairing the intracellular LPS signaling such as NF-kB activation, MyD88 expression and p38 phosphorylation [28][29][30][31]. Furthermore, since oral administration 20 mg/kg of ZM compounds showed antiinflammatory in carrageenan-induced rat paw edema within hours post administration [9] and modulated LPS-induced cytokine in mice spleen, these ZM compounds are readily bioavailable in blood and suggest proper pharmacokinetic properties for anti-inflammatory drugs.…”
Section: Discussionmentioning
confidence: 99%
“…A minimum of ten airways were observed in each section. The PAS positively-stained cells were counted and scored using previously described methods ( 16 , 17 , 18 ). The scoring method used was as follows: 0, <5%; l, 5–25%; 2, 25–50%; 3, 50–5%; and 4, >75% PAS positively-stained cells.…”
Section: Methodsmentioning
confidence: 99%